STUDY OF BIOLOGICALLY ACTIVE PARTICULARITIES OF PHEROMONE OF ANXIETY (THE SECRET) OF THE RED HYBRID WORM OF CALIFORNIA - Larisa CREMENEAC; Valentina ABRAMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of the study consisted in determining some biologically active properties of the pheromone of anxiety(secret), obtained from the tissues of the Red Hybrid Worm of California for the purpose of its use in veterinary medicine. The object of the research served: the Red Hybrid worm of California, the pheromone of anxiety both natively and in various dilutions (from 1:1 to 1:100). During the study, the following methods were used: to obtain the pheromone of anxiety and sterilizing of it; the determination of bactericidal activity and lysozyme was performed by the photonefelometry method. As a result of the research it was found that the pheromone of anxiety manifested bactericidal activity towards microbial cultures Staphylococcus aureus (№ 209), Escherichia coli, Micrococcus luteus (Micrococcus lysodeikticus), Candida albicans depending on the used dilutions. In the undiluted native secret, the bactiricidal activity, tested by using these crops, constituted respectively 552.00%, 355.00% and 13,500.00%, and in the dilutions 1:1 - 1:100 it oscillated respectively from 250.00%, 370.00% and 3,900.00% till 23.00%, 42.00% and 100.0%. Towards the microbian culture Candida albicans microbial activity was not found. The lysozyme activity of the undiluted pheromone of anxiety constituted 10.20%, and in the dilutions 1:10 - 1:100 it oscillated from 8.60% to 8.70%, which led to the fact that research would no longer be continued. Thus, it was found that the pheromone of anxiety, obtained from tissues of Red Hybrid worm of California, has manifested a bactericidal activity depending on the concentration and type of microbial cultures on which the test was performed.